Proposta de uma política pública de incentivo à saúde e segurança no trabalho para empresas de ônibus do transporte coletivo urbano de João Pessoa-PB. - Ferreira, Thiago Ribeiro (2014)
In Brazil, the Collective Urban Transport (TCU) is a public utility service is central to the economic, political and social development of cities. The promotion of health and safety (OHS) has been commitment of the government, which seeks to improve the environment and working conditions in the different sectors organizations. Public policy on OSH are considered means to encourage organizations to invest in risk prevention. One of these policies is the establishment of OHS requirements for public bids. In this dissertation, we seek to provide OSH items to be inserted into the bidding process for granting TCU service by bus from João Pessoa-PB. They were carried out interviews and document analysis to know the bidding process with a view to aspects of OSH. He was interviewed the management of one of the concessionaires to know the process of providing TCU service and applied a checklist to check the health and safety of workers. A literature review was conducted to identify items that can be inserted in the bidding process and contracts for the promotion of health and safety at work. It was found that in the bidding process there are no references to adopt technical standards of health and safety at work. In the company, it was noted that the focus of management is in fulfillment of what is established in the concession contract. As for the SST, it was noticed that there are failures in compliance with the rules of the Ministry of Labor and Employment (MTE). In the survey of incentives for OSH, they were found several mechanisms that could be inserted in the bidding process. Among them, there is the inclusion of safety standards items to be observed and the management system deployment OSH in organizations. It was concluded that the adoption of a public policy that encourages the promotion of health and safety by establishing OHS requirements for public procurement could result in a good performance by organizations, therefore, considering that the management of an organization that provides the public service is focused on meeting the determinations imposed in the bidding and contract, if there OHS requirements for public tenders, organizations would provide a healthy and safe environment for their workers.